Impaired participation of potassium channels and Na+/K+‐ATPase in vasodilatation due to reduced nitric oxide bioavailability in rats exposed to mercury. Issue 2 (1st October 2018) - Botelho, Tatiani; Marques, Vinícius B.; Simões, Maylla R.; do Val Lima, Patricia R.; Simões, Fabiana V.; Vassallo, Dalton V.; dos Santos, Leonardo
Abstract: Mercury intoxication is a public health risk factor due to its hazardous effect to several organs, including the cardiovascular system. There is evidence of endothelial dysfunction after exposure to mercury, but the effects on endothelium‐dependent vasodilatation are still unknown. In the present study, we aimed to evaluate the chronic effects of high HgCl2 doses on the mechanisms of vasodilatation. Wistar rats were injected with HgCl2 (1st dose 10.86 μg/kg, and daily doses 0.014 μg/kg for 30 days i.m.), and saline was used as control. Mercury exposure reduced the acetylcholine‐induced vasodilatation in aortic rings, which was restored by incubation with antioxidant tiron. Inhibition of the NO synthase, Na + /K + ‐ATPase and K + channels indicates reduced participation of these factors. In the mercury group, there were an increased local anion superoxide and a reduced NO. The vasodilatation to exogenous NO was partially inhibited by co‐incubation with TEA plus tiron, suggesting that reduced NO bioavailability is the responsible to that decreased the participation of K + channels. Moreover, there was an increased participation of the Na + /K + ‐ATPase associated with an up‐regulation of its alpha‐1 subunit. In conclusion, reduced NO bioavailability plays a major role in the impaired participation of K + channels and Na + /K + ‐ATPase in the acetylcholine‐mediated relaxation, although sodium pump is up‐regulated probably as a compensatory mechanism.